Evaluating India's possession of nuclear weapons: a study of India's legitimation strategies and the international responses between 1998-2008 - Kumari, D (2016)
The scope of the thesis is to study India's nuclear behavior and the international responses in the period following India's nuclear weapons tests in 1998 leading up to the waiver for India by the nuclear suppliers group in 2008. The thesis explores this process of nuclear reconciliation in the context of a quest for international nuclear legitimacy. Nuclear legitimation is understood as a two-sided process and the explanation assumes two sides to the story: the Indian side and the audience side. Grounding the conceptualization within a theoretical framework of constructivism, the thesis explores the legitimation strategies employed by the Indian government to assuage international apprehensions about its possession of nuclear weapons. Additionally, the thesis analyzes how and why selected states in the international audience received and responded to India's strategies. In doing so, the thesis acknowledges but goes beyond an apparent power and interest explanation underlined by geo-political/security considerations and economic/trade interests –to include an analysis of shared norms and beliefs that constituted a basis for legitimacy judgments, circumscribed the interaction between India and other states, induced certain responses on the audience side and made possible certain claims on the Indian side. The principal argument is that normative evaluations and ideational factors served as important resources on both sides and also played an important role in determining the timing as well as the nature of nuclear reconciliation with India. By allowing a strategic employment of different arguments that appealed to the different states in the targeted audience, a legitimation process reduced the political, economic and diplomatic costs for the Indian government. Similarly, it enabled other states in the audience to support (as the P3: France, Russia and United Kingdom did), not come in the way (as the game-changers: Australia, Canada, Germany and Japan did) or not block India-specific waiver (as the white knights: Ireland, Austria, Norway, New Zealand, Sweden and Switzerland did)— and to justify their responses, cost-effectively.